2005
DOI: 10.2139/ssrn.644101
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Comparables for the Valuation of European Firms

Abstract: Abstract:This paper investigates which comparables selection method generates the most precise forecasts when valuing European companies with the enterprise value to EBIT multiple. We also consider the USA as a reference point. It turns out that selecting comparable companies with similar return on assets clearly outperforms selections according to industry membership or total assets. Moreover, we investigate whether comparables should be selected from the same country, from the same region, or from all OECD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
3
Order By: Relevance
“…The construction of multiples based on a target company's industry classification is a common phenomenon (Nel et al, 2013a;Nel, 2009a;2009b;Goedhart et al, 2005;Liu, Nissim and Thomas, 2002a;Fernández, 2001;Barker, 1999). So, too, is a multiples-based valuation approach where peer groups are based on valuation fundamentals (Henschke and Homburg, 2009;Dittmann and Weiner, 2005;Goedhart et al, 2005;Herrmann and Richter, 2003;Bhojraj and Lee, 2002). The methodology applied in this paper is largely adopted from Nel et al (2013a, b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of multiples based on a target company's industry classification is a common phenomenon (Nel et al, 2013a;Nel, 2009a;2009b;Goedhart et al, 2005;Liu, Nissim and Thomas, 2002a;Fernández, 2001;Barker, 1999). So, too, is a multiples-based valuation approach where peer groups are based on valuation fundamentals (Henschke and Homburg, 2009;Dittmann and Weiner, 2005;Goedhart et al, 2005;Herrmann and Richter, 2003;Bhojraj and Lee, 2002). The methodology applied in this paper is largely adopted from Nel et al (2013a, b).…”
Section: Methodsmentioning
confidence: 99%
“…The premise of the proponents of industry classification as a basis for peer group selection is that companies operating in similar industries will have similar profitability, growth and risk profiles. The second school of thought argues that peer group selection should be based on companies with similar valuation fundamentals (Dittmann and Weiner, 2005;Goedhart, Koller and Wessels, 2005). The premise of the proponents of valuation fundamentals as a basis for peer group selection is that companies with similarly sized economic variables will have similar profitability, growth and risk profiles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Cheng & McNamara (2000) reported that the use of earnings per share -the relevant criterion for selecting the appropriate P/E and P/BV multiples. Dittmann and Weiner (2005) recommend the use of return of assets (ROA) as a selection criterion for the EV/EBIT multiples in the similar study. Penman & Zhang (2006) analyzed the effect of sustainable earnings on the P/E multiple.…”
Section: Introductionmentioning
confidence: 99%
“…Se, por um lado, o analista perde os benefícios de uma análise mais completa e complexa, proporcionada pelo método do FDC, por outro há a conveniência de obter uma avaliação com resultados satisfatórios sem incorrer em grandes esforços em termos de custos e tempo (Bhojraj & Lee, 2002). Além disso, é possível avaliar mais de uma empresa ao mesmo tempo e, nesse sentido, sua popularidade é atribuída à simplicidade, se comparada a outros métodos (Dittmann &Weiner 2005).…”
Section: Introductionunclassified